A Study of the Seven Habits Among Teachers of Highly Educated and Motivated People in Government Schools in Palestine - Jarad, Nashaat Abu; Ahmad, Jamilah; Tahir, Lokman Mohd; Jambari, Hanifah (Edukasi, 2020)
Guru yang hebat dalam organisasi sekolah, karena mereka berkontribusi pada prestasi siswa, hasil sekolah, dan pertumbuhan pendidikan nasional. Penelitian ini dilakukan untuk mengkaji esensi tindakan dan motif tujuh orang yang sangat produktif di kalangan guru di Beit Lahia, Gaza. Analisis terhadap tujuh kebiasaan orang yang sangat sukses dipandang sebagai penghasut. Penelitian ini menggunakan pendekatan kuantitatif, dan 70 responden memperoleh kumpulan kuesioner. Guru sekolah negeri di Beit Lahia, Gaza, adalah responden laporan ini. Versi 24.0 dari Program Statistik Sosial Sains (SPSS) digunakan untuk mengevaluasi data yang ringkas dan inferensial. Lupakan frekuensi, persentase dan rata-rata, statistik deskriptif digunakan. Statistik inferensi yang meliputi uji-T, uji ANOVA satu arah, dan Uji Korelasi Pearson digunakan untuk menjawab semua hipotesis penelitian. Berdasarkan temuan penelitian, rata-rata rata-rata untuk tingkat praktik tujuh perilaku orang yang sangat sukses (min = 3,24) dan tingkat motivasi (min = 2) ditunjukkan. Selain itu, hasil juga mengungkapkan perbedaan substansial (p 0,05) untuk praktik tujuh perilaku individu yang dipengaruhi gender yang sangat produktif. Hasil penelitian juga mengungkapkan bahwa tidak ada hubungan penting antara praktik perilaku tujuh orang yang sangat sukses dengan tingkat motivasi guru di sekolah negeri Beit Lahia, Gaza. Simpulan penelitian ini dapat menjadi penting untuk membantu guru merefleksikan dan menguraikan kinerja mereka sendiri dan menghasilkan materi pembelajaran yang baru digunakan dalam konteks mereka.Great teachers in a school organization, as they contribute to student achievement, school results, and national education growth. This research is conducted to examine the essence of the actions and motives of seven highly productive people among teachers in Beit Lahia, Gaza. The analysis of the seven extremely successful people's habits is seen as inciting. This research uses quantitative approaches, and 70 respondents obtained a collection of questionnaires. The government schoolteachers in Beit Lahia, Gaza, are respondents to this report. Version 24.0 of the Science Social Statistics Program (SPSS) was used to evaluate concise and inferential data. Forget frequency, percentage and mean, descriptive statistics were used. Inference statistics which included T-test, one-way ANOVA test and Pearson Correlation Test were used to address all the study hypotheses. Based on the research findings, the average mean for practice level of seven highly successful people(s) behaviors (min = 3,24) and motivation level (min = 2) was shown. Furthermore, the results also revealed substantial differences (p 0.05) for the practice of seven behaviors of highly productive gender-affected individuals. The results also revealed that there is no important association between the practice of seven highly successful people (s) behaviors and the level of teacher motivation in the Beit Lahia, Gaza, state schools. The results of this study can be is important to help teachers to reflect and elaborate on their own performances and produce as a result learning material to be newly utilized in their contexts.